Chains as a Way of Living - Enrico, Nicole (2024)
In a context of greater financing for conservation projects with a focus on territorial market development in the Peruvian Amazon, this research seeks to understand how the livelihoods of indigenous women producers can configure the dynamics of value chains through their trajectories. Therefore, the present study is based on the experience of the community of Shampuyacu, where the NGO Conservation International intervenes through agreements and conservation projects. Specifically, the case of the Bosque de las Nuwas Association and its tourism and infusion value chain initiatives will be analyzed. To analyze this case, we describe the dynamics of the chain, characterize the configuration of women’s livelihoods, and analyze how the association of women’s different assets and the trajectories they have in the value chain is interrelated to its dynamics. The qualitative and exploratory study finds that women’s trajectories differ by virtue of their social assets, mediated by ethnicity and relations between clans, the generalized context of gender violence, and support systems for care. Regarding human assets, the level of education can define the adoption of leadership in the chain or generate exclusion, causing conflicts. Finally, the use of natural assets such as family gardens can be an opportunity to scale up the chain, but the lack of coordination between actors doesn’t make it possible.